Durability of Cognitive Behavioral Therapy Effects for Youth and Adolescents With Anxiety, Depression, or Traumatic Stress:A Meta-Analysis on Long-Term Follow-Ups. Issue 1 (January 2019) - Rith-Najarian, Leslie R.; Mesri, Bita; Park, Alayna L.; Sun, Michael; Chavira, Denise A.; Chorpita, Bruce F.
Abstract: Cognitive behavioral therapies (CBT) for youth with anxiety, traumatic stress, and depression have demonstrated strong effects in individual studies and meta-analyses. Relatively more attention has been given to posttreatment effects, though, and assessment of follow-up effects has been limited at the meta-analytic level. The current meta-analysis aimed to (a) examine the effects of youth CBT at posttreatment, 1-month, 3-month, 6-month, 1-year, and long-term (2 + years) follow-up as well as (b) identify research-related variables (e.g., measure respondent type) that relate to effects. Using a random effects model across 110 child and adolescent CBT groups, within-group effect sizes were large at posttreatment ( g = 1.24) and from 1-month through long-term follow-up ( g = 1.23–1.82), and effect sizes did not significantly differ by treatment target (i.e., anxiety, traumatic stress, depression). However, availability of outcome data for effect sizes diminished across later follow-up assessments. Moreover, effect sizes were significantly associated with outcome respondent type across assessment timing, with outcome measures from caregiver and youth respondents associated with smaller effect sizes ( B = -0.97, p < 0.001) relative to outcome measures that were evaluator-reported. Results provide initial support for the durability of treatment effects for youth CBTs and highlight the importance of some confounding variables. Implications for improving treatment research standards and prioritizing assessment of long-term follow-up assessment are discussed. Highlights: Within-group effect sizes were large at post-treatment (1.24) through 2 + year follow-up (1.82) Follow-up effect sizes did not vary by treatment target type Follow-up effect sizes did vary by outcome respondent type Outcome data for later follow-ups was scarce and confounded by research-related variables